Assessment of the Level of NT-proBNP in Patients with Arterial Hypertension Aged 80 Years and Older, Depending on the Presence of Heart Failure and Senile Asthenia Syndrome - V A. Safronenko; A. I. Chesnikova (SINAPS LLC, 2024)
Objectives. To evaluate the informativeness of the N-terminal brain-promoting natriuretic peptide (NT-proBNP) for the diagnosis of chronic heart failure (CHF), depending on the presence of senile asthenia syndrome (SSA) in patients with arterial hypertension (AH) 80 years and older.Materials and Methods. 320 patients with hypertension, depending on the presence of CHF and SSA, were divided into groups: group 1A - patients with hypertension, SSA and CHF (n=84), group 1B - patients with hypertension, SSA without CHF (n=77), group 2A - patients with hypertension, CHF without SSA (n=84), group 2B - patients with hypertension without CHF and without SSA (n=75). The CSA was identified by the questionnaire "Age is not a hindrance". The level of NT-proBNP was determined in blood serum by enzyme immunoassay. ROC analysis was used to determine the threshold value of markers.Results. In patients with hypertension and SSA without CHF, the concentration of NT-proBNP in the blood is 2.3 times higher (p=0.003) compared with patients with hypertension without SSA and without CHF, which indicates the effect of SSA on the level of NT-proBNP. In patients with hypertension and CHF without SSA, the level of NT-proBNP is 4.3 times higher compared with patients with hypertension without SSA and without CHF (p<0.001), in whom the concentration of NT-proBNP was noted below the threshold level (106.2 pg/ml). In patients with hypertension and SSA and CHF, the highest concentrations of NT-proBNP were recorded, which are 2.9 times (p<0.001) higher than in "fragile" patients with hypertension without CHF and 1.5 times higher than in "strong" patients with hypertension and CHF (p<0.001). A new threshold level of NT-proBNP has been calculated for the diagnosis of CHF in patients with hypertension and SSA aged 80 years and older - 365.9 pg/ml.Conclusion. For the diagnosis of CHF in patients with hypertension 80 years and older without CSA, the NT-proBNP marker is informative, since, according to the data obtained, its level did not depend on the age of the patients. When using NT-proBNP to detect CHF in patients with hypertension and SSA 80 years and older, the calculated threshold marker level (365.9 pg/ml) should be used, since in these patients the concentration of NT-proBNP is increased, regardless of the presence of CHF.